Inhibition of human leukocyte and porcine pancreatic elastase by homologues of bovine pancreatic trypsin inhibitor. - Kraunsoe, J; Claridge, T; Lowe, G (1996)
The interactions of three BPTI homologues with human leukocyte elastase and porcine pancreatic elastase have been investigated. The principal mutation in determining the specificity of inhibition was the Lys15-Val mutation at the P1 position. An additional mutation at P3, i.e., BPTI (Lys15-Val, Pro13-Ile), increased the inhibition of HLE to a Ki = 2.5 x 10(-10) M, but decreased the inhibition of PPE, showing this to be a useful site for improving selectivity. Kinetic evidence suggests that the inhibition of HLE by BPTI homologues probably takes place by a two-step mechanism in which an isomerization step occurs after initial binding. 1H NMR spectroscopy of the BPTI (Lys15-Val) and BPTI (Lys15-Val, Pro13-Ile) mutants indicates that small conformational changes are associated with the mutations, but these are localized in the immediate vicinity of the mutation in the outer binding loop and in the inner loop connected to it through the Cys14-Cys38 disulfide bridge.